Radford Ranch - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
A panoramic view of Radford Ranch. Orchards and homes are visible. Some of the trees in the orchards have their trunks painted white. In the left foreground is a prominent terrace with decorative planters. In the center foreground of the photograph is a clothesline with clothes hanging. A square structure that appers to be filled with water can be seen towards the center of the photograph. Mountains stretch across the distant background.